Strength and morphological behavior of glass-carbon/epoxy hybrid composite plates aging in seawater, engine oil and diesel fuel degradation environment - Saylik, Ahmet; Temiz, Semsettin (Springer Heidelberg, 2024)
In this study, glass/epoxy (GFRP), carbon/epoxy (CFRP) and glass-carbon/epoxy hybrid (GCFRP) composites were aged in seawater, engine oil and diesel fuel degradation environments for 30, 60 and 90 days. The effect of aging environment and time on the structural strength of the composite was examined by applying tensile, three-point bending and low-velocity impact tests to aged composites. Scanning electron microscopy analyses were compared to detect fracture damage occurring in the internal structure of the composites. It was concluded that the degradation environment that most affects the mechanical strength of composites is seawater. Degradation resistance is improved due to the glass/carbon hybridization effect. It has been determined that the glass-carbon hybridization effect in GCFRP composites significantly changes their mechanical strength compared to GFRP and CFRP composites stacked alone. By comparing the glass-carbon hybridization effect in CFRP composites with GFRP and CFRP composites stacked alone, their advantages under different tests are clearly emphasized.
Keywords: Hybrid composite; Woven fiber; Impact strength; Degradation; Aging process; Morphological analysis